Analisis Representasi Sosial dalam Wisata Religi - Salva Valeska; Heri Puspito Diyah Setiyorini; Rijal Khaerani (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Religious tourism is growing as a very important social phenomenon, especially in communities that have a strong culture and religion. This growth has made religious places not only seen as sacred places, but also as tourist destinations that involve social interaction and the way people give meaning. This study aims to analyze the social picture of religious tourism and understand how visitors construct the meaning of religious tourist attractions based on their experiences. This research uses a qualitative method by collecting data through in-depth interviews and observations. The data were analyzed using social picture theory supported by phenomenological approaches and symbolic interactionism. The results of the study show that religious tourism is seen as a place that combines spiritual, cultural, social, and recreational aspects. Religious tourist attractions are considered not only as places of worship, but also as areas for contemplation, learning, socializing, and enjoying beauty. The image is formed through shared knowledge, individual experiences, and social interactions that occur while traveling. This study concludes that the social picture of religious tourism is variable and context-dependent, reflecting the ongoing negotiation between sacred values and tourism practices.